Plant–Fungal Interactions: A Case Study of Epicoccoum nigrum Link - Rafał Ogórek; Katarzyna Przywara; Agata Piecuch; Magdalena Cal; Agnieszka Lejman; Krzysztof Matkowski (Plants, 2020)
Epicoccum nigrum Link is a cosmopolitan species, and it has been described as both an in vitro and in vivo antagonist of many fungal pathogens of plants. However, there are no clear reports about the interactions between E. nigrum and various plant species, and about the effects of culture filtrates produced by this fungus on plants. Therefore, we assessed the interactions between E. nigrum and different plant species, such as sugar beet (Beta vulgaris L. ssp. vulgaris), spring wheat (Triticum aestivum L.), red clover (Trifolium pratense L.), and winter oilseed rape (Brassica napus L.). Additionally, we evaluated the effect of E. nigrum culture filtrates on garden cress (Lepidium sativum L.). Our study showed that the E. nigrum strains varied in terms of the color of excreted culture filtrates and showed different interactions with garden cress. Overall, fungal strains only affected adversely the sprout length in a significant way and, partially, the growth of the tested plant. In addition, we confirmed the suitability of the garden cress as a test plant in in vitro toxicological tests. Most strains of E. nigrum (61.1%) secreted enzymes expected to participate mainly in the later stages of the infection (amylases and proteases) and not those expected to operate in the early phases of host penetration (cellulases and pectinases) that were secreted by 33.3% of fungal strains. The group of pectinolytic enzymes represented the catalysts with the highest activity. Host specialization tests showed that E. nigrum was mainly re-isolated from the plant surface and the number of infected seedlings as well as the disease index depended on a studied plant species, with sugar beet and red clover being most sensitive to infection. In turn, the lowest value of the disease index caused by E. nigrum strains was recorded for spring wheat and winter oilseed rape. Overall, statistically significant differences in the growth of plant seedlings during the host specialization test were noted only for sugar beet and red clover seedlings. The seedlings of plants in the control group (without fungal inoculum) exhibited an increased length compared to those treated with E. nigrum inoculum. Our studies also showed that E. nigrum is probably a facultative saprotroph of plants and it may winter on red clover, which is presumably its main reservoirs, among the species considered.